Fostering harmony: Key factors in promoting interfaith unity within the Dayak Ngaju Community in Palangka Raya - Jeniva, Isabella; Netanyahu, Kurniawan; Alvin, Jeck Thomas (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2025)
The Palangka Raya City community, initially dominated by the Dayak Ngaju community, now tends to be more diverse. However, this diversity is now disturbed, especially by the issue of religious harmony, where several internal conflicts have occurred between religious communities. Based on this phenomenon, this research examines important elements that can help build unity and relations between religious communities in the Dayak Ngaju community in Palangka Raya. In this research, data collection was carried out through interviews and documentation studies. The study results indicate that six main factors contribute to increasing harmony: local customs and culture, education and counseling, legitimacy and credibility of traditional and religious figures, relations between religious communities and cultures, social and political conditions, and leadership with integrity. These factors complement each other in maintaining a balance between local traditions and the challenges of modernization so that the Dayak Ngaju community can maintain harmony amidst diversity. Collaboration between the government, Damang, and religious figures is the main key to preventing conflict and strengthening social stability. This research contributes to the formulation of national and regional policies related to efforts to increase harmony and mitigate potential conflicts from a socio-cultural perspective.